PELATIHAN PEMBUATAN DAN PENGGANTIAN WARNA COVER KONVENSIONAL DENGAN MICROSOFT WORD PADA MA YPI BATANG KUIS - Nita Syahputri; Ulfah Indriani; Anggia Nikita Hutabarat (Universitas Methodist Indonesia, 2021)
The purpose of community service activities is to implement the Tri Dharma of Higher Education and provide learning how to make and replace conventional cover colors with Microsoft Word at Madrasah Aliyah (MA) Yayasan Pendidikan Islam (YPI) Batang Kuis. A paper is a work that is written, has a scientific nature and contains a discussion on a particular topic. In making a paper, it is necessary to have a good cover so that it can attract the interest of the reader. A conventional cover is a cover that is made attractively using features from Microsoft Word. There are still many who think that Microsoft Word can only be used to type documents. In fact, the latest Microsoft Word update can be used for other things too, one of which is for making conventional covers. Through training for MA YPI Batang Kuis students, it is hoped that they can use Microsoft Word to make conventional paper covers as a support in the teaching and learning process.